Association of vitiligo and metabolic syndrome: a case control study - Thakur, Priyanka; Mehta, Karaninder S.; Chauhan, Pushpinder S.; Singh, Ravinder; Sharma, Anju L.; Sharma, Anuj; Sharma, Reena; Kumar, Prabal; Vashist, Sanket; Manvi, Sujaya; Kukreja, Amisha; Negi, Rohit (International Journal of Research in Dermatology, 2023)
Background: Vitiligo is an acquired disorder of depigmentation which involves skin and mucous membranes characterized by development of well-defined white macules on skin, mucosa and overlying hair of the skin can be involved. Systemic nature of the vitiligo might lead to insulin resistance metabolic profile abnormalities. Objective was to study the association between vitiligo and metabolic syndrome. Methods: The study was done in department of dermatology, venereology and leprosy of Dr. R. P. Government Medical College Kangra (Tanda), Himachal Pradesh. The study included 150 cases and 150 controls. Cases: age above 18 years with a diagnosis of vitiligo were included in the study. Pregnant and lactating women were excluded. Patients who had used medications that could affect the metabolic status (like systemic steroid therapy or cyclosporine or on hormonal replacement therapy). Patients already on lipid lowering agents and antidiabetic drugs. The case group was further subdivided into three subgroups according to VIDA score (group A: 1-0, group B: 1-2 and group C: 3-4). Controls: those visiting outdoor patient department and admitted for minor day care procedures Clinical details of patients were recorded regarding age, sex, smoking/alcohol consumption. General physical examination includes height, weight, body mass index, waist circumference, blood pressure. All the patients and controls were subjected to following tests: fasting blood sugar (FBS), cholesterol (CHOL), triglyceride (TAG), low density lipoprotein (LDL), high density lipoprotein (HDL), very low-density lipoprotein (VLDL), fasting serum insulin level (FSIL). Venous samples were taken after 12 hours of fasting. The participants were screened for metabolic syndrome as per national cholesterol education program adult treatment panel III (NCEP ATP III). Metabolic syndrome rates were compared between case and control groups. Results: The mean age was 35.82±12.9 years among cases and 36.97±11.76 years among controls. The M/F ratio of cases being (1:1.6) and controls (1:1). The mean duration of vitiligo was 117.8±105.5 months. Metabolic syndrome was significantly prevalent amid vitiligo cases 74 (49.3%) as compared to controls 23 (15.3%) with OR (95% CI) =5.37 (3.1-9.3). Metabolic syndrome was more frequent in VIDA subgroup 3{71 (47.3%)} and was statistically significant (p≤0.001). Conclusions: The study found association of metabolic syndrome among vitiligo patients. In addition, the study also found that in non-segmental vitiligo, frequency of metabolic syndrome was higher as compared to another pattern. Furthermore, frequency of metabolic syndrome increased as activity of vitiligo increased in the study.